Medicines support and social prescribing to address patient priorities in multimorbidity (MIDAS): protocol for a definitive, multi-arm, cluster randomised, controlled trial in Irish general practice - Susan M Smith; Fiona Boland; Frank Moriarty; Molly Byrne; Farah Tahsin; Barbara Clyne; Paul Doody; Laura O’Connor; Paddy Gillespie; Bridget Kiely; Andrew W Murphy; Eanna Kenny (BMJ Open)
Background There is increasing awareness of the impact of living with multiple long-term conditions (referred to as multimorbidity) on patients and health systems. Managing multimorbidity remains a challenge for primary care providers; necessitating tailored interventions that are both clinically and cost effective. In the Irish health system, two pilot trials have demonstrated promising results for patients living with multimorbidity. The first, MultimorbiditY COllaborative Medication Review And DEcision making (MyComrade), involved pharmacists supporting the management of polypharmacy, and the second, Link MultiMorbidity (LinkMM), involved link workers delivering social prescribing. This definitive trial aims to evaluate the clinical and cost effectiveness of both these interventions, as well as conduct a process evaluation.Methods This is a pragmatic, multi-arm, definitive, cluster randomised controlled trial in Irish general practices. The trial will include three arms: (1) MyComrade; (2) LinkMM and (3) usual care, acting as an efficient shared control arm for both interventions. For this trial, 672 patients will be recruited from 48 general practices. The eligibility criteria for the patients will be: (1) over 18 years of age; (2) has two or more chronic conditions; (3) taking 10 or more regular medicines and (4) attending their general practice team for chronic disease management. Outcome data will be collected for all participants, across all trial arms at baseline and 6 months. Primary outcomes include the number of medicines (reflecting the MyComrade intervention) and patient capability (reflecting the LinkMM intervention). Secondary outcomes include proportions and types of potentially inappropriate medications, patient experience of care, patient activation, self-rated health, health-related quality of life, mortality and healthcare utilisation. Quantitative and qualitative data will be collected to inform the process evaluation. Additionally, an economic evaluation will be conducted to evaluate the cost-effectiveness of both interventions compared with the control arm.Ethics and dissemination The trial protocol was approved by the Irish College of General Practice (ICGP) Ethical Review Board (ref: ICGP_Rec_2023_016). A formal knowledge dissemination plan has been developed for the trial, which includes peer-reviewed publications, conference presentations and reports to healthcare professionals, commissioners and policymakers.Trial registration number ISRCTN11585238.